2007
DOI: 10.1182/blood-2006-08-044149
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle–dependent oscillation of GATA2 expression in hematopoietic cells

Abstract: In vitro manipulation of hematopoietic stem cells (HSCs) is a key issue in both transplantation therapy and regenerative medicine, and thus new methods are required to achieve HSC expansion with self-renewal. GATA2 is a transcription factor controlling pool size of HSCs. Of interest, continuous overexpression of GATA2 does not induce HSC proliferation. In this report, we demonstrate that GATA2 expression, in leukemic and normal hematopoietic cells, oscillates during the cell cycle, such that expression is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Therefore, it is important to clarify the molecular mechanisms involved in the control of GATA2 levels. Although cellular GATA2 levels are regulated by transcriptional control and proteasome-mediated degradation (37,38), ubiquitin E3 ligase, which ubiquitylates GATA2 to promote degradation via the ubiquitin-proteasome system, has not been identified. In the present study, we demonstrated that GATA2 is a novel CPD-dependent substrate for Fbw7.…”
mentioning
confidence: 99%
“…Therefore, it is important to clarify the molecular mechanisms involved in the control of GATA2 levels. Although cellular GATA2 levels are regulated by transcriptional control and proteasome-mediated degradation (37,38), ubiquitin E3 ligase, which ubiquitylates GATA2 to promote degradation via the ubiquitin-proteasome system, has not been identified. In the present study, we demonstrated that GATA2 is a novel CPD-dependent substrate for Fbw7.…”
mentioning
confidence: 99%
“…GATA2 expression oscillates during the cell cycle such that expression is high in the S phase but low in G1/S and M phases. 32 Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of hematopoietic cells have suggested that GATA2 expression varies during the cell cycle and that GATA2 regulates cell-cycle regulators. 32,33 We, therefore, evaluated whether the cell cycle was altered in BM-MSC in which GATA2 expression was inhibited. The number of cells present in G1/G0 was significantly increased when GATA2 expression was decreased (Figure 4), which was due to the significantly increased proportion of cells in the G1 phase (Online Supplementary Figure S4).…”
Section: Enrichment Of Cell Cycle Regulatory Genes Based On Transcripmentioning
confidence: 99%
“…Activity-level fluctuations are also theorized to play important roles in protein and gene regulation and adaptation (Day 2009;Gerland and Hwa 2009;Henzler-Wildman and Kern 2007). In addition to stochastic fluctuations, GATA1 levels are known to oscillate in response to the cell cycle, and it is well-known that oscillatory behavior is exhibited in a wide range of biomolecular systems (Koga et al 2007;Goldbeter 1996). In fact, the hematopoietic stem cell activity is linked to the biological rhythms of the circadian cycle (Mendez-Ferrer et al 2008).…”
Section: Introductionmentioning
confidence: 99%